Regional developments [in 2021 Global Food Policy Report] - International Food Policy Research Institute; Benin, Samuel; Andam, Kwaw S.; Ulimwengu, John M.; Abay, Kibrom A.; Breisinger, Clemens; Elsabbagh, Dalia; Ibrahim, Hosam; Kamaly, Ahmed; Raouf, Mariam; Akramov, Kamiljon T.; Romashkin, Roman; et al. (International Food Policy Research Institute, 2021)
As the coronavirus pandemic reached every corner of the world in 2020, countries responded rapidly with an array of policies to stop the spread of the highly contagious disease, and then with social and economic policies to protect food security, incomes, and livelihoods. This experience brought attention to weaknesses in health, economic, and social protection systems. But it also showcased new innovations, approaches, and the surprising resilience of food systems. The diverse experiences of the world’s major regions have important lessons for creating sustainable, equitable, efficient, healthy, and resilient food systems. The impact of COVID-19 on food systems, wellbeing, and future transformation is examined for each major region.